Sorption studies of semi-crystalline polyamides - Ruppa Subramanian, Shalini. (2010)
Sorption is the penetration and dispersion of a gas or liquid molecule through a solid surface such as a polymer. Sorption studies were undertaken to analyse the effect of the sorbent on polymers. In this experiment, the weight gained by polymers and the diffusion coefficient of acetone was studied on polyamide 6, polyamide 66, polyamide 11 and polyamide 12.